Ecoenzymatic stoichiometry and microbial nutrient limitation in rhizosphere soil in the arid area of the northern Loess Plateau, China - Cui, Yongxing; Fang, Linchuan; Guo, Xiaobin; Wang, Xia; Zhang, Yanjiang; Li, Pengfei; Zhang, Xingchang (Soil biology & biochemistry, 2018)
Arid ecosystems are characterized as having stressful conditions of low energy and nutrient availability for soil microorganisms and vegetation. The rhizosphere serves as the one of most active microorganism habitats, however, the general understanding of the ecoenzymatic stoichiometry (exoenzymes) and microbial nutrient acquisition in rhizosphere soil is limited. Here, we investigated the vegetation communities and determined the soil physicochemical properties, microbial biomass, and enzymatic activities in rhizosphere under different vegetation and soil types in the arid area of the northern Loess Plateau. Type Ⅱ standard major axis (SMA) regression analysis showed that the plants played a more important role than soil properties in determining ecoenzymatic stoichiometry. Linear regression analysis displayed a microbial stoichiometric homeostasis (community-level) in rhizosphere. The Threshold Elemental Ratio (TER) revealed that the microbial nutrient metabolisms of rhizosphere were co-limited by N and P in the A. ordosica and A. cristatum communities of loess, and A. cristatum communities of feldspathic sandstone weathered soil. Binding spatial ordination analysis (RDA and CCA) demonstrated that soil physical properties (e.g., soil moisture, silt and clay contents) have more contribution to ecoenzymatic stoichiometry than the other investigated soil parameters, whereas soil nutrients (e.g., total organic carbon, nitrogen, and phosphorus) predominantly controlled microbial nutrient ratios. Therefore, the ecoenzymatic stoichiometry in rhizosphere is greatly regulated by plants and soil physical properties. The microbial N and P are co-limited under Gramineae plant in loess and feldspathic sandstone weathered soil regions. Meanwhile, the microbial nutrient limitation is mainly affected by soil nutrient supply. These findings could be crucial for illuminating rhizosphere microbial metabolism and revealing the nutrient cycling of root-soil interface under arid and oligotrophic ecosystems. [Display omitted] •Plant is more crucial in determining rhizospheric enzyme stoichiometry than soil.•Gramineae has strong effect on enzyme stoichiometry.•Microbial metabolisms were co-limited by N and P.•Microbial nutrient ratios depend on soil nutrients supply.